Progress Report to the International Monetary and Financial Committee on the Activities of the Independent Evaluation Office of the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
This report describes recent follow-up on past Independent Evaluation Office (IEO) evaluations, summarizes the update of the 2006 evaluation of multilateral surveillance, and outlines the ongoing evaluations. It raises the concern that progress in implementing Board-endorsed IEO recommendations has been quite mixed, suggesting the need for further consideration to reinforcing the follow-up process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet